The Influence of Accounting Information System Usage and Human Resource Quality on the Performance of Micro and Small Enterprises in Tana Duen Village - Plewan, Aleksander Paskalinus; Dince, Maria Nona; Romario , Fransiscus De; Tokan, Maria Goreti Mao (Neo Journal of economy and social humanities, 2025)
Based on the research conducted, the topic studied was the influence of the use of Accounting Information Systems (AIS) and the quality of Human Resources (HR) on the performance of Micro and Small Enterprises (MSEs) in Tana Duen Village. The purpose of this study is to analyse whether these two factors have a significant effect on improving MSE performance. The method employed is a quantitative approach using multiple linear regression analysis, where data were collected through questionnaires distributed to MSE actors in the village. The research results indicate that although the use of Accounting Information Systems (AIS) does not have a significant effect on the performance of Micro, Small, and Medium Enterprises (MSMEs), the quality of human resources has a considerable impact, with entrepreneurs who possess good skills and take responsibility demonstrating better performance. Furthermore, this study also found that the combined use of AIS and human resource quality has a significant impact on the performance of MSMEs. The contribution of this research provides valuable insights for the development of MSMEs in Indonesia, particularly regarding the importance of enhancing human resource capacity and optimising the use of accounting technology to improve performance.